AUTOMATED CONTROL SYSTEM AND MONITORING BY TECHNOLOGICAL PROCESSES BY PRODUCTION OF POLYMERIC AND BITUMINOUS TAPES ON THE BASIS OF APPLICATION OF SCADA OF SYSTEM - A. S. Kirienko (Системный анализ и прикладная информатика)
Expediency of use of a control system and monitoring of technological processes of production is proved in article that will allow to lower work expenses, and also to increase productivity due to the best production process.The main objective of system, remote monitoring is that gives the chance far off and to quickly give an assessment to the current situation on production, to accept reasonable and timely administrative decisions.